Rancang Bangun Sistem Self-Order Berbasis Android untuk CRM Operasional UMKM Kuliner - Sabila Rosad; Herbert Siregar; Asep Wahyudin (LKP KARYA PRIMA KURSUS, 2026)
Culinary Micro, Small, and Medium Enterprises (MSMEs) still face challenges in the ordering process, such as manual order recording, long queues, and limited management of order data. These conditions highlight the need for digital transformation to improve operational efficiency and service quality. This study aims to design and develop an Android-based self-order system for culinary MSMEs as a form of ordering process digitalization and as an implementation of operational Customer Relationship Management (CRM). The research method applied is system development, including literature study, requirement analysis, system design, implementation, and testing. The system adopts a client–server architecture, with an Android application as the client and a FastAPI-based backend integrated with a PostgreSQL database. The application allows customers to view menus, add items to a cart, enter customer identity, and place orders independently without user authentication. System testing is conducted using black-box testing to validate functional requirements. The results indicate that the developed self-order system operates properly in supporting digital ordering processes, improving operational efficiency, and facilitating the implementation of operational CRM through structured order data management. This system is expected to serve as a practical solution for culinary MSMEs in managing digital ordering and customer interactions.